PENDEKATAN HUMANISTIK DALAM PENGKAJIAN ISLAM DI KELAS IV MADRASAH IBTIDAIYAH NAHDLATUL WATHAN KARANG BATA - Rizki Isma Wulandari (Bajang Institute, 2023)
This research is aimed at: (1) examine the reasons for the fourth grade teacher at MI NW Karang Bata to apply a humanistic approach to the study of Islam in learning aqidah morals, (2) to examine the implementation of the humanistic approach in Islamic studies at MI NW Karang Bata. The research method in this article uses a qualitative approach with a descriptive type. This research was conducted at MI NW Karang Bata, Mataram City, Lombok. The research phase consists of: (1) data collection, (2) data reduction, (3) data presentation, (4) drawing conclusions. The results of this study are: 1) there are reasons why teachers apply a humanistic approach in studying Islam because a) the humanistic approach in education becomes more meaningful, b) creates harmonious, comfortable and happy interactions with students, and c) students become more valued. 2) The implementation of a humanistic approach in Islamic studies at MI NW Karang Bata has been implemented through the madrasa culture, namely the